Implementing Information System Innovations to Manage Biosecurity Issues in Australian Food NetChains - Storer, Christine; Noonan, John; Murray-Prior, Roy; Batt, Peter (Society for Global Business & Economic Development (SGBED), 2011)
Tracking and tracing systems are being demanded by customers such as the major Australian supermarket chains, superior food service chains and globally in export markets such as the European Union and Asia. This includes the ability to track products as they move to downstream customers and to traceback where products have been sourced for feedback and to resolve problems. To continue to access these global premium priced markets Australian food organisations need to ensure they meet changing customer requirements. Traditionally information communication technologies to provide tracking and tracing systems have been set up for larger business and industry sectors that warrant the costs of development. Small business cannot always afford to invest in the infrastructure to establish through chain and industry wide netchain based systems. This problem is compounded where businesses are fragmented and spread over large geoographical areas even if they have similar requirements. An action learning approach was taken to identify what is needed in setting up tracking and tracing systems to address biosecurity issues in three small business based netchains (livestock 'A' and fruits 'B' and 'C'). In the livestock 'A' sector fears of a global pandemic has heightened the need for tracking and traceablity processes, combined with preventative actions and rigorous bio-security protocols (e.g. traceability of traffic properties). For fruit 'B' and 'C' movements of produce across state and national borders requires phytosanitary certification to provide assurance to minimize or eradicate the spread of diseases and pests. Concerns or delays in tracking and tracing can result in perishable produce becoming unsalable. A system was identified to suit small businesses and those in niche market industries. The system was based on deployment through the internet. The system had to link in with existing business information systems and business methods, be reliable, able to be tailored to address biosecurity issues and effective in meeting customer requirements. Results presented compare the use of the tracking and tracing system across the three different sectors (animal and horticultural products) and states of Australia. Findings are presented on what was learnt in the process including: identifying business in chains and networks to work collaboratively with; catalysts needed to get commitment to change; and support systems needed for successful implementation across multiple small businesses linked in netchains.